Navigating the Light-Sheet Image Analysis Software Landscape: Concepts for Driving Cohesion From Data Acquisition to Analysis - Gibbs, Holly C.; Mota, Sakina M.; Hart, Nathan A.; Min, Sun Won; Vernino, Alex O.; Pritchard, Anna L.; Sen, Anindito; Vitha, Stan; Sarasamma, Sreeja; McIntosh, Avery L.; Yeh, Alvin T.; Lekven, Arne C.; et al. (Frontiers in Cell and Developmental Biology, 2021)
From the combined perspective of biologists, microscope instrumentation developers, imaging core facility scientists, and high performance computing experts, we discuss the challenges faced when selecting imaging and analysis tools in the field of light-sheet microscopy. Our goal is to provide a contextual framework of basic computing concepts that cell and developmental biologists can refer to when mapping the peculiarities of different light-sheet data to specific existing computing environments and image analysis pipelines. We provide our perspective on efficient processes for tool selection and review of the current hardware and software commonly used in light-sheet image analysis, as well as discuss what ideal tools for the future may look like.